2011
DOI: 10.1021/ja207985w
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Kinetics, and Photochemistry of β-Strand Association and Dissociation in a Split-GFP System

Abstract: Truncated green fluorescent protein (GFP) that is refolded after removing the 10th beta strand can readily bind to a synthetic strand to fully recover the absorbance and fluorescence of the whole protein. This allows rigorous experimental determination of thermodynamic and kinetic parameters of the split system including the equilibrium constant and the association/dissociation rates, which enables residue-specific analysis of peptide-protein interactions. The dissociation rate of the noncovalently-bound stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 20 publications
(34 reference statements)
3
77
0
Order By: Relevance
“…60,61 In this paper, we describe a simple two-state model Hamiltonian that can describe the potential energy and the charge-transfer dependence of monomethine dyes at different detuning from the cyanine limit. The model is a generalized Mulliken-Hush electron transfer model, 62,63 wherein the diabatic state energies and electron transfer matrix element are coupled to twisting displacements about the methine bridge bonds.…”
Section: Introductionmentioning
confidence: 99%
“…60,61 In this paper, we describe a simple two-state model Hamiltonian that can describe the potential energy and the charge-transfer dependence of monomethine dyes at different detuning from the cyanine limit. The model is a generalized Mulliken-Hush electron transfer model, 62,63 wherein the diabatic state energies and electron transfer matrix element are coupled to twisting displacements about the methine bridge bonds.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique can generate misleading results, because the GFP complexes, after being formed and fluorescing, are bound irreversibly, which can be highly perturbative to the processes being studied, especially if the protein interaction being probed is ordinarily reversible (6). Although split GFP complexes essentially do not dissociate spontaneously after they are formed, we have discovered that dissociation into a peptide and a truncated protein can be induced by light irradiation in certain cases (7). Photodissociation introduces the possibility of active control of protein-protein interactions with light.…”
mentioning
confidence: 99%
“…Boxer and co-workers have demonstrated that GFP can undergo photo-induced displacement and exchange of bstrand 10 [49,50] (Figure 1c). This exchange can be used to shift GFP's emission from green to yellow fluorescence due to the presence of Tyr203 (associated with yellow emission) on one copy of b-strand 10 (s10 T203Y ), but not the one that is exchanged with (s10 WT ).…”
Section: Light-driven Fp-based Biosensormentioning
confidence: 97%